MULTITIME ACTION RECURRENCES ON A MONOID - Ghiu, Cristian; Udrişte, Constantin; Tuligă, Raluca (Ann. Sofia Univ. Fac. Math. and Inf., 2016)
The discrete multitime multiple recurrences are common in analysis of algorithms, computational biology, information theory, queueing theory, filters theory, statistical physics etc. We discuss in detail the cases of recurrences on a monoid, highlighting in particular algebraical aspects and original theorems on existence and uniqueness of solutions.